2019
DOI: 10.1021/acsami.9b05554
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Glycerol–Water Hydrogel for Biomimetic Human Skin with Resistance Memory Function

Abstract: Biomimetic human skinlike materials with preferably self-healing ability, high sensitivity for external stimuli, and good adhesiveness against diverse substrates under a wide range of temperatures are of great importance in various applications such as wearable devices, human-motion devices, and soft robotics. However, most of the reported biomimetic human skinlike materials lack memory function, i.e., they cannot memorize the external stimuli once the stimuli disappear. This drawback hinders their application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 54 publications
0
69
0
Order By: Relevance
“…Flexible and stretchable sensors are attracting significant interest in a wide range of applications including health monitoring, diagnostic devices, soft robotics, and electronic skins. [ 1–6 ] Piezoresistive sensors, one of the main types of sensors, change their resistance in response to mechanical deformation and have demonstrated a number of applications in monitoring strain, [ 4–8 ] pressure, [ 6,7,9 ] flow, [ 10–12 ] and temperature. [ 4,13,14 ] To meet the requirements for both human motion detection and biosafety, flexible sensors should be biocompatible.…”
Section: Introductionmentioning
confidence: 99%
“…Flexible and stretchable sensors are attracting significant interest in a wide range of applications including health monitoring, diagnostic devices, soft robotics, and electronic skins. [ 1–6 ] Piezoresistive sensors, one of the main types of sensors, change their resistance in response to mechanical deformation and have demonstrated a number of applications in monitoring strain, [ 4–8 ] pressure, [ 6,7,9 ] flow, [ 10–12 ] and temperature. [ 4,13,14 ] To meet the requirements for both human motion detection and biosafety, flexible sensors should be biocompatible.…”
Section: Introductionmentioning
confidence: 99%
“…[ 24 ] As a result, the P(MAH‐β‐CD‐ co ‐NIPAM)/f‐BNNS hydrogels possessed excellent strength and tensile strain, making it superior to the majority of the reported PNIPAM‐based hydrogels (Figure 5e). [ 2,16–20,32 ] Moreover, the tensile strain of the P(MAH‐β‐CD‐ co ‐NIPAM)/f‐BNNS hydrogel is much higher than those of most nanocomposite hydrogels, which indicated that f‐BNNSs are ideal nanofillers because of strong dynamic interactions between f‐BNNSs and PNIPAM matrix. [ 26 ]…”
Section: Resultsmentioning
confidence: 99%
“…Recently, several nanofillers have been introduced PNIPAM hydrogels to improve mechanical or swelling properties. [ 2,16–19 ] For example, Xu and co‐workers reported a nanofiller‐reinforced hydrogel by combing biocompatible boron nitride nanosheets (BNNSs), clay, and PNIPAM. With 0.16 wt% BNNSs, the tensile strength of PNIPAM hydrogel was increased from 0.02 to 0.04 MPa, increasing by 100%.…”
Section: Introductionmentioning
confidence: 99%
“…[47] The bands at 1601 and 1456 cm −1 could be associated with the benzene ring vibration of PSDVB. [45,48,49] The absorption peaks at 667 and 723 cm −1 were Scheme 1. Schematic description of the preparation of Fe@PSDVB and its application.…”
Section: Surface Morphology and Characterizationmentioning
confidence: 99%